Tata Ruang Kantor di Sekertariat Dewan Perwakilan Rakyat Daerah Kota Surabaya (Studi pada Bagian Rapat dan Perundang-Undangan) - Laskar Intifada Saifullah Fatah Wardana; Dian Arlupi Utami (Universitas Negeri Surabaya, 2023)
The office is a place for employees to carry out their professional activities. The purpose of this research is to analyze office layout, analyze the application of office layout principles, and identify factors in the office environment at the Secretariat of the Regional Representatives Council of the City of Surabaya (Study on the Meetings and Legislation Section). This research uses a descriptive qualitative method approach. Data sources include primary and secondary data, data collection is done through observation and interviews. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study illustrate that: (1) the form of office layout uses a combined office layout form, but besides that there is a dividing partition which makes the room seem crowded and narrow and separates the Head of Section's room from the employees. (2) The principles of office layout, such as the shortest distance, working sequence, and changing the arrangement of the workplace have not been optimally implemented. Employees experience difficulties in accessing work equipment. (3) work environment factors. Suggestions that can be recommended are (1) Gradual overhaul of office layout by removing parapets so that rooms become more flexible, (2) Office spatial principles to support the effectiveness of work completion, and make changes to the arrangement of workplaces to make them more diverse (3) office environmental factors, namely increasing the number of lights and air conditioners, and providing sound insulation so that employees are comfortable while working. Keywords:OfficeSpatialForms,OfficePrinciples,OfficeEnvironmental Factors